Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) standardized template for collection of key information for benefit-risk assessment of live-attenuated viral vaccines. Issue 49 (17th November 2020) - Gurwith, Marc; Condit, Richard C.; Excler, Jean-Louis; Robertson, James S.; Kim, Denny; Fast, Patricia E.; Drew, Stephen; Wood, David; Klug, Bettina; Whelan, Mike; Mallett Moore, Tamala; Khuri-Bulos, Najwa; et al.
Abstract: Several live-attenuated viral vaccine candidates are among the COVID-19 vaccines in development. The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) has prepared a standardized template to describe the key considerations for the benefit-risk assessment of live-attenuated viral vaccines. This will help key stakeholders assess potential safety issues and understand the benefit-risk of such vaccines. The standardized and structured assessment provided by the template would also help to contribute to improved communication and support public acceptance of licensed live-attenuated viral vaccines.